Frequency of Molar-Incisor Hypomineralization in Children Visiting Department of Operative Dentistry & Endodontics at Hamdard University Dental Hospital Karachi - Lalani, Hussain Bahadur Ali; Ali, Syed Abrar; Rafique, Rida; Shahid Ali, Dua; Us Saqib Siddiqui, Hafiz Najm (Biological and Clinical Sciences Research Journal, 2025)
Molar-incisor hypomineralization (MIH) is a prevalent developmental dental condition affecting the first permanent molars and incisors, leading to enamel defects, hypersensitivity, and increased risk of dental caries. Early detection is essential for timely management and prevention of complications. Objective: To determine the frequency of molar-incisor hypomineralization (MIH) in children visiting the Department of Operative Dentistry & Endodontics at Hamdard University Dental Hospital Karachi with complain of pain & sensitivity. Methodology: This cross-sectional study was conducted over six months and included 180 children presenting with complaints of pain, sensitivity, discoloration, or caries in one or more first permanent molars with or without involvement of incisors. Participants were selected using consecutive sampling. The diagnosis of MIH was based on criteria set by the European Academy of Paediatric Dentistry (EAPD). It included clinical examination for demarcated opacities, post-eruptive enamel breakdown, atypical restorations, and extractions of first permanent molars. Informed consent and assent were obtained from participants and their guardians. Data analysis was performed using SPSS Version 23, with quantitative data summarized as means and standard deviations and qualitative data as frequencies and percentages. Chi-square and Fisher’s exact tests were used for associations, with significance set at p ≤ 0.05. Results: The mean age of participants was 11.66 ± 2.73 years. The prevalence of MIH was 3.9%. Demarcated opacities were observed in 2.8% of participants, post-eruptive enamel breakdown in 2.2%, atypical restorations in 1.7%, and extractions of first permanent molars in 1.7%. MIH was more common in females (71.4%) than males (28.6%), and 85.7% of cases occurred in the 8–12-year age group. However, no significant associations were found between MIH and age or gender. Conclusion: The study highlights a low prevalence of MIH in the local population, with most cases occurring in younger children. Early diagnosis and intervention are crucial to managing this condition effectively and preventing long-term complications.